Inspiraling halo accretion mapped in Ly α emission around a z ∼ 3 quasar. Issue 3 (25th September 2017) - Arrigoni Battaia, Fabrizio; Prochaska, J. Xavier; Hennawi, Joseph F.; Obreja, Aura; Buck, Tobias; Cantalupo, Sebastiano; Dutton, Aaron A.; Macciò, Andrea V.
Abstract: In an effort to search for Ly α emission from circum- and intergalactic gas on scales of hundreds of kpc around z  ∼ 3 quasars, and thus characterize the physical properties of the gas in emission, we have initiated an extensive fast survey with the Multi-Unit Spectroscopic Explorer (MUSE): Q uasar S napshot O bservations with MU se: S earch for E xtended U ltraviolet e M ission (QSO MUSEUM). In this work, we report the discovery of an enormous Ly α nebula (ELAN) around the quasar SDSS J102009.99+104002.7 at z  = 3.164, which we followed-up with deeper MUSE observations. This ELAN spans ∼297 projected kpc, has an average Ly α surface brightness SBLy α  ∼ 6.04 × 10 −18  erg s −1  cm −2  arcsec −2 (within the 2σ isophote) and is associated with an additional four previously unknown embedded sources: two Ly α emitters and two faint active galactic nuclei (one type-1 and one type-2 quasar). By mapping at high significance, the line-of-sight velocity in the entirety of the observed structure, we unveiled a large-scale coherent rotation-like pattern spanning ∼300 km s −1 with a velocity dispersion of <270 km s −1, which we interpret as a signature of the inspiraling accretion of substructures within the quasar's host halo. Future multiwavelength data will complement our MUSE observations and are definitely needed to fully characterize such a complex system. None the less, our observations reveal the potential of new sensitive integral-field spectrographs to characterize the dynamical state of diffuse gas on large scales in the young Universe, and thereby witness the assembly of galaxies.